Experimental Evaluation of Antidiabetic Effect of Punica Granatum Peel Extract against Streptozotocin Induced Diabetes in Albino Rats - Dr. Shakira Fathima Syeda; Dr. Mohammed Mohsin (International Journal of Pharma and Bio Sciences, 2020)
Abstract: Diabetes mellitus is a disease characterised by derangement in carbohydrate, protein and fat metabolism which is caused by the complete or relative insufficiency of insulin secretions. Plants and their bioactive constituents are used for the treatment of diabetes mellitus throughout the world; especially in countries where access to the conventional treatment of diabetes mellitus is inadequate. The present study was undertaken to investigate the anti-diabetic effect of Punica granatum ethanolic peel extract in STZ induced diabetic rat. STZ was used to induce diabetes in albino rats weighing 150-250 grams. The fasted diabetic rats were divided in to 6 groups of 6 animals each. Group I Normal control group received distilled water 5 ml/kg body weight orally daily, Group II were treated with STZ 50mg/kg body weight induced diabetic rats were served as diabetic control group and were treated with distilled water orally daily until diabetes occur, Group III i.e STZ induced diabetic rats were served as standard group and were treated with Glibenclamide at a dose of 0.5 mg/kg body weight orally daily. Group IV & Group V Punica granatum ethanolic peel extract was administered with 100mg/kg and 200mg/kg dose orally. This study was conducted over a period of 15 days with oral administration of drugs and the plant extract which was started on the 6th day of STZ treatment. The fasting blood glucose levels were determined on day 0, 5th, 10th, and 15th day by using glucometer. The maximum reduction in Blood Glucose level was observed at a dose of 200mg/kg body weight. Data were statistically analyzed by Student “t” Test. P<0.001 was considered as highly significant.